(untitled) (Journal of Oriental Studies, 2016)
This article is made versatile analysis of the structure of proposals in the text of classic books. Given some information about the stylistic turns, which are not found in modern Chinese, through examples indicate their place in the proposals and the value in the texts of ancient Chinese classic books.